Diabetes Remission after Nonsurgical Intensive Lifestyle Intervention in Obese Patients with Type 2 Diabetes - Adham Mottalib; Mahmoud Sakr; Mohamed Shehabeldin; Osama Hamdy (Journal of Diabetes Research)
Partial or complete remission from type 2 diabetes was recently observed after bariatric surgeries. Limited data is available about the possibility of inducing diabetes remission through intensive weight reduction. We retrospectively evaluated diabetes remissions after one year of the Weight Achievement and Intensive Treatment (Why WAIT) program, a 12-week intensive program for diabetes weight management in real-world clinical practice. Among 120 obese patients with type 2 diabetes who completed the program, 88 patients returned for follow-up at one year. Nineteen patients (21.6%) had major improvement in their glycemic control, defined as achieving an A1C <6.5% after one year. Four patients (4.5%) achieved either partial or complete diabetes remission defined as A1C <6.5% and <5.7%, respectively, on no antihyperglycemic medications for one year; 2 achieved partial remission (2.3%) and 2 achieved complete remission (2.3%). At the time of intervention, patients who achieved diabetes remission had shorter diabetes duration (<5 years) and lower A1C (<8%) and were treated with fewer than 2 oral medications. They achieved a weight reduction of >7% after 12 weeks. These results indicate that a subset of obese patients with type 2 diabetes is appropriate for intensive lifestyle intervention with the aim of inducing diabetes remission.